2020
DOI: 10.1017/dsj.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating design uncertainties in additive manufacturing using design artefacts: examples from space industry

Abstract: The use of metal Additive Manufacturing (AM) has increased in recent years with potential benefits for novel design solutions and efficient manufacturing. In order to utilise these potentials, engineers need to address uncertainties related to product design and the AM process. This paper presents a design process utilising product-specific AM Design Artefacts (AMDAs) to assess uncertainties identified during design. The process emphasises the importance of concurrently developing the product and AM knowledge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…The findings showed that it would be beneficial to consider qualification as early as possible in order to design components that can be qualified, especially when designing for a new manufacturing process like AM. The second study focused on understanding how engineers can improve how they design components for AM, while at the same time developing an understanding for the AM process [59]. The findings showed that specific uncertainties related to the design and the AM process are beneficially explored, tested and evaluated by using part-specific artefacts.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings showed that it would be beneficial to consider qualification as early as possible in order to design components that can be qualified, especially when designing for a new manufacturing process like AM. The second study focused on understanding how engineers can improve how they design components for AM, while at the same time developing an understanding for the AM process [59]. The findings showed that specific uncertainties related to the design and the AM process are beneficially explored, tested and evaluated by using part-specific artefacts.…”
Section: Methodsmentioning
confidence: 99%
“…The studies are hence referenced in the description of the framework where appropriate. The overall research process is shown in Figure 2 where the time frame for collection of the different data are indicated, as is the completion of the related papers [1,22,59]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations